Colonizing Russia's Promised Land Orthodoxy and Community on the Siberian Steppe - Friesen, Aileen (University of Toronto Press, 2019)
Russia's political elite promoted the colonization of Siberia as a means of transforming the Russian empire into an international economic power, making possible the exploitation of Siberia's resources, particularly its rich farmland. The state's invitation to resettle was readily accepted in many communities in European Russia. Millions of peasant-settlers trekked across the empire for the opportunity to find affordable land, a luxury that their villages could not offer. Friesen highlights the role of Orthodoxy as a cultural force in transforming Russia's imperial periphery through settler colonialism; the religious meaning ascribed by settlers, clergymen, and state officials to these new settlements and the surround territory; and the cracks of modern Russian society, which could not be glossed over by the nationalistic rhetoric of Orthodox-driven settler colonialsm.